A Bibliometric Analysis of Job Rotation on Employee Experience - Putri Fadillah, Raysha Naya (West Science Interdisciplinary Studies, 2025)
Job rotation has gained increasing attention as an effective strategy to enhance employee experience and career development. This study uses bibliometric analysis to examine the evolution of job rotation research, identifying key publication trends, influential journals, and important contributors in this field. Data was collected from Google Scholar, covering publications from 1951 to 2025. The findings reveal that job rotation is important in skill enhancement and organizational productivity. However, adaptation stress and decreased motivation require structured implementation and supportive training programs. The study also highlights the interdisciplinary nature of job rotation research, linking it to employee well-being, organizational behavior, and human resource development. The results of this study provide insights for organizations looking to optimize job rotation policies to improve workforce adaptability and engagement.